Parafoveal vessel Density Dropout May Predict Glaucoma Progression in The Long-Term Follow Up - Kurysheva, Natalia Ivanovna; Shatalova, Ekaterina Olegovna (Journal of Ophthalmology and Research, 2022)
Relevance: Successful glaucoma monitoring strongly depends on its progression prediction with the search for new clinical biomarkers. Purpose: To study new progression predictors of primary open angle glaucoma (POAG). Materials and methods: The 2-year clinical data of 85 POAG patients were prospectively analyzed. Optical coherence tomography-angiography was used to assess retinal microcirculation. Retrobulbar blood flow was assessed using color Doppler imaging. Functional progression was determined using Humphrey perimetry trend and event analyses, and structural loss – by means of SD-OCT negative slope of retinal nerve fiber layer and ganglion cells complex (GCC). The area under the receiver operating characteristic curve (AUC), the Wald Chi-Squared test of the generalized logistic mixed models and the multilevel mixed-effects models analysis were applied to differentiate between progression and non-progression eyes. A clinical biomarker was considered to be a predictor if the disease progression was confirmed by both perimetry and SD-OCT. Results: Vessel density (VD) of the parafoveal superficial plexus (AUC 0.776±0.07; Wald Chi-Squared test 12.5), macular thickness measured from the internal limiting membrane to the inner plexiform layer (0.751±0.06; 12.8), peak follow-up intraocular pressure (0.768±0.07; 9.3), end-diastolic velocity (EDV) of central retinal artery (0.715±0.11; 6.29), mean ocular perfusion pressure (0.682±0.08; 5.6) and focal loss volume of GCC (0.636±0.08; 5.0) were detected as significant predictors of glaucoma progression. According to the multilevel mixed-effects models analysis, only four predictors were determined: VD of the parafoveal superficial plexus (z -4.77), EDV of central retinal artery (z -3.08), focal loss volume of GCC (z 3.53) and peak follow-up intraocular pressure (z 3.20).